Highly Sensitive Photoacoustic Imaging: A New Strategy for Ultrahigh Spatial Resolution Seismic Physical Model Imaging - Xin Liu; Wen Wang; Qiangzhou Rong; Baozhi Yu (IEEE Photonics Journal, 2020)
Seismic-physical-model imaging (SPM), a successful strategy for the research in seismic wave propagation and wave theoretical predictions, effectively bridges the computation modeling and the field exploration and leads to a nearly ideal setting without a rock matrix. However, the current strategy for SPM imaging, the ultrasonic imaging technology, shows a narrow excitation frequency and a low coupling efficiency, which strongly limit the resolution of the image. Herein, laser ultrasonic imaging strategy, an imaging strategy which merges the large penetration depth of ultrasound imaging and high contrast of optical imaging, is developed for SPM imaging for the first time, where photoacoustic (PA) effect is utilized for the excitation. A customized contrast agent, Co3O4 nanoflake arrays (CONAs), is designed for this special application of photoacoustic imaging in a large-scale via a facile hydrothermal method. The PA properties of the as-prepared CONAs are investigated with both theoretical and experimental methods. The results demonstrate the CONAs enhance the response signal over 16 times due to the strong light absorption, high photoacoustic-to-acoustic transformation efficiency and excellent thermal stability of the CONAs. By applying PA technology with the assistance of CONAs, 3D SPM images with high resolution are achieved.